'From small acorns do great oak trees grow' - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
SPORE does not normally publish readers. letters, but we are making an exception in this issue because the following letter contains both important information and a word of encouragement for all of us at SPORE. To the Editor SPORE Sir, I am obliged...